lnc-MRGPRF-6:1 Promotes M1 Polarization of Macrophage and Inflammatory Response through the TLR4-MyD88-MAPK Pathway - Hu, Dan; Wang, Yuzhong; You, Zhihuan; Lu, Yingfei; Liang, Caihong (Mediators of Inflammation, 2022)
Background. Macrophage-mediated inflammation plays an essential role in the development of atherosclerosis (AS). Long noncoding RNAs (lncRNAs), as crucial regulators, participate in this process. We identified that lnc-MRGPRF-6:1 was significantly upregulated in the plasma exosomes of coronary atherosclerotic disease (CAD) patients in a preliminary work. In the present study, we aim to assess the role of lnc-MRGPRF-6:1 in macrophage-mediated inflammatory process of AS. Methods. The correlation between lnc-MRGPRF-6:1 and inflammatory factors was estimated firstly in plasma exosomes of CAD patients. Subsequently, we established lnc-MRGPRF-6:1 knockout macrophage model via the CRISPR/Cas9 system. We then investigated the regulatory effects of lnc-MRGPRF-6:1 on macrophage polarization and foam cell formation. Eventually, transcriptome analysis by RNA sequencing was carried out to explore the contribution of differential genes and signaling pathways in this process. Results. lnc-MRGPRF-6:1 was highly expressed in the plasma exosomes of CAD patients and was positively correlated with the expression of inflammatory cytokines in plasma. lnc-MRGPRF-6:1 inhibition significantly reduced the formation of foam cells. The expression of lnc-MRGPRF-6:1 was upregulated in M1 macrophage, and lnc-MRGPRF-6:1 knockout decreased the polarization of M1 macrophage. lnc-MRGPRF-6:1 regulates macrophage polarization via the TLR4-MyD88-MAPK signaling pathway. Conclusions. lnc-MRGPRF-6:1 knockdown can inhibit M1 polarization of macrophage and inflammatory response through the TLR4-MyD88-MAPK signaling pathway. lnc-MRGPRF-6:1 is a vital regulator in macrophage-mediated inflammatory process of AS.